LITERASI DIGITAL BAGI UMKM - S, Lydia Rosintan; Soeharjoto; Dewi, Rosiyana (Belalek, 2023)
Digital literacy is an inseparable part of information. Information is no longer only in printed form, but can now be accessed using digital media. Digital literacy is an urgent need for today's society. Because technological progress that is not balanced by intelligence in using modern technological devices will undoubtedly have a negative impact on human civilization. With current technological developments, we must be able to make the best use of it. However, because the process of disseminating data in the digital world is very rapid, we are required to be able to filter information so as not to get wrong information. MSMEs also play a role in the distribution of development results and are the driving force behind the growth of national economic activity. Attention to the development of the MSME sector gives its own meaning to efforts to reduce a country's poverty rate. The existence of positive opportunities means that MSME players have enormous potential to be successful in the market, if they can adopt the right marketing strategy. This is what encouraged SMKS Pelita IV students and SME groups in the Tambora area, West Jakarta, to start learning to build small businesses in local residential areas. In this PKM activity, SMKS Pelita IV students help with training and counseling to develop their business. The Community Service Team (PKM) of the Faculty of Economics and Business, Trisakti University will hold training to better introduce marketing strategies, especially digital marketing, in this case Social Media, to students of SMKS Pelita IV Tambora, West Jakarta. to increase sales of their products.